RESEARCH FEATURES OF AEROELASTIC OSCILLATIONS OF UNMANNED AERIAL VEHICLES WITH ELECTRIC ACTUATOR OF RUDDERS - A. V. Bykov; S. G. Parafes; V. I. Smyslov (Научный вестник МГТУ ГА, 2018)
Designing a modern flight vehicle is associated with the need to solve many scientific and technical problems. These tasks include the prevention of insecure self-oscillations in flight, taking into account the elasticity of the structure. These problems relate to dynamic aeroelasticity, a science that examines the interaction of an elastic structure (at its oscillation) with an air flow. Maneuverable unmanned aerial vehicles (UAVs) are considered. Since UAVs are essentially not used without an automatic control system (ACS), its presence must be taken into account when considering the vibrations of an elastic structure in flight. The influence of the elasticity of UAV design on the operation of ACS in flight is manifested in the possibility of self-oscillations in the loop "elastic UAV – ACS". Self-oscillations lead to disruption of normal operation of the onboard equipment or its failure. The complexity of the problem requires its consideration at almost all stages of UAV’s development, including the creation of a prototype and testing. The computational and experimental studies of the characteristics of elastic oscillations in the UAV flight of the cross-shaped scheme are considered. The features of these UAVs (options with a modular design, the nonlinearity of the airframe, rudders, ACS, and others) due to a significant amount of testing that is the basis for the calculations. Electric actuators have a small continuous operation time, and resource use, there are gearboxes with a large gear ratio and backlashes. This determines the dependence of the rotation rigidity of the rudders on the amplitude and frequency, as well as a significant increase in the total moments of inertia. The technique of bench experiment with obtaining data to assess the boundaries of the flutter and the boundaries of the stability of the loop "elastic UAV – ACS" is given. The questions of improvement of the stabilization system of UAV required for the study of its stability at frequencies of elastic oscillations are considered, as well as the evaluation of the limiting cycles of self-oscillations is given.